Impact of environmental regulations on manufacturing industries in the U.K and India, with general focus on key factors - Mathew, Rinosh (2008)
The previous literature on environmental regulations and its impact is very vast and varied. Environmental regulations came into being sometime between 1850s and 1900s.However its importance has recently been realised. Many companies are now trying to manage the risks that are inherent in their line of operation due to changing regulations. This paper deals with these changes influenced by regulations with focus on manufacturing industries. Ever, since this topic has come into prominence. There has been number of papers highlighting the significance of regulations and its impact. However, this paper is different and has a different approach to the subject than the previous, more quantitative, research in that it follows a qualitative research methodology of semi-structured interviews followed by a Thematic Analysis of these interviews, which has previously not been undertaken. The aim of this research is to investigate and understand the different Impacts of environmental regulations on manufacturing industries with general focus on key factors. The key factors being, Financial performance, Environmental management systems, Productivity, Innovations, Green markets, and Managerial attitude. It was found very much in conformance to previous studies that financial performance decreases, environmental management system was better developed, increased focus to sustainable innovations, pollution abatement expenditure rose, productivity decreased, management attitude bettered and new development of a green market was initiated. Therefore, the research calls for more attention and work on environment and the industry as manufacturing actors have a potential to find stronger incentives for going green.